Comparative Analysis of Hemodynamic Effects of Remimazolam and Propofol Combined with Esketamine in Colonoscopic Procedures in the Elderly - Deng BR; Zhang Y; Xie ZF; Wang DD; Zeng T; Zhang DB; Huang L; Wang QY; Shen T; Wu QL (Dove Medical Press, 2024)
Bo-Ran Deng,1,* Yang Zhang,2,* Zi-Feng Xie,3,* Ding-Ding Wang,4,* Tao Zeng,1 Dong-Bo Zhang,3 Li Huang,1 Qi-Yan Wang,1 Tu Shen,3 Qiao-Ling Wu3 1Surgical Anesthesia Center, Zigong Hospital of TCM, Zigong, 643000, People's Republic of China; 2Department of Anesthesia, Da'an District Maternal and Child Health Hospital, Zigong, 643000, People's Republic of China; 3Department of Anesthesia, The First Affiliated Hospital of Jinzhou Medical University, Jinzhou, 121000, People's Republic of China; 4Department of Anesthesia, EYE & ENT Hospital of Fudan University, Shanghai, 200031, People's Republic of China*These authors contributed equally to this workCorrespondence: Tu Shen; Qiao-Ling Wu, Department of Anesthesia, the First Affiliated Hospital of Jinzhou Medical University, No. 40, Section 3, Songpo Road, Linghe District, Jinzhou, 121000, People's Republic of China, Email shentu2011@sina.com; wqiaoling2013@sina.comPurpose: The debate continues over the differential impact of remimazolam vs propofol on hemodynamic stability. This study aims to elucidate the effects of a combination of remimazolam and esketamine vs propofol and esketamine on hemodynamic parameters in elderly patients undergoing painless colonoscopies.Patients and Methods: We conducted a randomized controlled trial involving 754 patients, divided equally between two treatment groups. The remimazolam-esketamine group (RE group) received 0.15 mg/kg of remimazolam and 0.3 mg/kg of esketamine. Conversely, the propofol-esketamine group (PE group) was administered 1.5 mg/kg of propofol with 0.3 mg/kg of esketamine. Primary outcomes focused on the incidence of hypotension. Secondary outcomes assessed were other hemodynamic adverse events, intraoperative blood pressure and heart rate fluctuations, usage of vasoactive agents, sedation efficacy, and additional adverse reactions.Results: Hypotension occurred significantly less frequently in the RE group (9.78%, 95% confidence interval[CI]: 6.67- 12.87%) compared to the PE group (23.57%, 95% CI: 21.22- 30.52%), P< 0.001. The RE group also showed lower incidences of sinus tachycardia, sinus bradycardia, and required less support from vasoactive agents (P< 0.001). Additionally, the RE group experienced smaller fluctuations in blood pressure and heart rate (P< 0.05). Both groups achieved a 100% sedation success rate. Notably, the RE group had a longer induction period but a quicker recovery time (P< 0.001), and lower rates of respiratory depression (P=0.006) and injection pain (P< 0.001).Conclusion: Remimazolam combined with esketamine offers superior hemodynamic stability and significantly reduces adverse event rates compared to propofol plus esketamine in elderly patients undergoing painless colonoscopies, while maintaining effective sedation.Keywords: remimazolam, esketamine, colonoscopy, elderly patients, hemodynamic effects